A current study of psychological well-being in educational institutions: A systematic literature review - Mukhlis, Hamid; Hariri, Hasan; Riswandi, Riswandi; Haenilah, Een Yayah; Sunyono, Sunyono; Maulina, Dina; Fitriadi, Fitriadi (Journal of Education and Learning (EduLearn), 2024)
The issue of psychological well-being in education has emerged as an increasingly critical topic in recent years. This is due to the significance of psychological well-being in enhancing the performance of e ducational institutions, encompassing students, teachers, and the process of formulating school policies. This study sought to discover recent research on psychological well-being from an academic perspective. A total of 27 research articles were successfully gathered and reviewed based on the established criteria. This article review was conducted utilizing two databases (SCOPUS and WoS) and the following keywords: "psychological well-being" combined with "AND" and other search terms such as "school", "teacher", and "student". This systematic review offers a synthesis of results that can serve as the initial step in developing constructs of psychological well-being in educational institutions, thus implying the importance of psychological well-being for teachers and students. The results of the analysis from this systematic literature review have been discussed and concluded in this study.